Query engine for blockchain applications based on smart contracts - Noha Ahmed Thabet (2022)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2022 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Informatics-IFM; Dissertation, Academic